Spectral Lags and Characteristic Time Scales of GRBs with Known Redshift - Eda Sonbaş; Dilem Göktaş; İlham Nasıroğlu (Journal of Advanced Research in Natural and Applied Sciences)
In this study, we extracted two key prompt emission parameters, i.e., spectral lags and characteristic time scales, and investigated their potential correlation. The minimum variability time scale (MTS) was determined using a wavelet-based method, while spectral lag analysis was conducted via the cross-correlation function (CCF) to examine the temporal properties of 162 gamma-ray bursts (GRBs) with known redshifts observed by the Swift/BAT satellite between 2011 and 2019. The analysis suggests short-duration bursts exhibit a shorter variability time scale than long-duration bursts. Although the MTS value for most long- and short-duration GRBs is shorter than T90, a few cases approach the equality limit. Additionally, long-duration bursts tend to have a higher spectral lag than short-duration bursts. We found spectral lag values consistent with zero within their uncertainties for short-duration GRBs. Spectral lags exhibit a strong positive correlation with MTS and a negative correlation with the isotropic peak luminosity (Liso), with slopes of 1.01 ± 0.04 and -1.13 ± 0.20, respectively.